Edukasi Gangguan Menstruasi Pada Remaja Di Kelas VII-A SMP 13 Padang - Hasanalita, Hasanalita; Permatasari, Putri; Satria, Epi (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2024)
The highest incidence of sexually transmitted infections (STIs) in the world occurs in teenagers and young adults. In Indonesia, teenage girls experience vaginal discharge every year. Health education through lecture and discussion methods carried out by planning, implementing and evaluating activities. This community service activity was carried out in Class VII A-B of SMP Negeri 13 Padang for 30 young women. The form of activity is providing health education through lecture and discussion methods, in the form of material about menstruation with the help of power point slides, distributing leaflets, and videos of the physiology of menstruation in women. The material provided is providing information about the concept of menstruation, menstrual phases, menstrual disorders, and efforts to maintain reproductive hygiene during menstruation. Then, after delivering the material, a discussion session continues, where students are asked to ask questions and respond to them in order to find out their understanding of the material provided. There was an increase in female students' knowledge before and after receiving menstrual education materials.